PENGARUH KEBIJAKAN BAURAN PEMASARAN UNIVERSITAS BUNDA MULIA TERHADAP KEPUTUSAN MAHASISWA UNTUK KULIAH DI UNIVERSITAS BUNDA MULIA - Arko Pujadi (Business Management Journal, 2017)
This research tries to found out the effect from the marketing mix of Bunda Mulia University to student’s decision to college in Bunda Mulia University. Students in generally said that Bunda Mulia University already has sufficient marketing mix policy. This opinion arose from the academic facilities and services. From correlation analysis, this research found that there are two variables of marketing mix which has significant effect to student’s decision. Those variables are, academic facilities and services and promotion.This research is conducted to find out the effect of the marketing mix of Bunda Mulia University onto each student’s decision to enroll in Bunda Mulia University. In general, the students stated that Bunda Mulia University already had sufficient marketing mix policy. From the correlation analysis, this research found that there are two variables of marketing mix-which have the significant effect onto the student’s decision. Those variables are academic facility along with services and promotion.Key WordsMarketing Mix, student, and correlation